2010
DOI: 10.1103/physreva.82.032326
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement dynamics in three-qubitXstates

Abstract: I explore the entanglement dynamics of a three qubit system in an initial X-state undergoing decoherence including the possible exhibition of entanglement sudden death (ESD). To quantify entanglement I utilize negativity measures and make use of appropriate entanglement witnesses. The negativity results are then extended to X-states with an arbitraty number of qubits. I also demonstrate non-standard behavior of the tri-partite negativity entanglement metric, its sudden appearance after some amount of decoheren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 31 publications
2
48
0
Order By: Relevance
“…quantum correlations eventually decohere, as expected for three subsystems subject to local dissipation such as dephasing or depolarizing channels [34]. This is in marked contrast to two-qubit baths where the antidiagonal components ofρ E that appear in Eqs.…”
Section: General Case: Master Equations For N-qubit Environmentsmentioning
confidence: 80%
See 1 more Smart Citation
“…quantum correlations eventually decohere, as expected for three subsystems subject to local dissipation such as dephasing or depolarizing channels [34]. This is in marked contrast to two-qubit baths where the antidiagonal components ofρ E that appear in Eqs.…”
Section: General Case: Master Equations For N-qubit Environmentsmentioning
confidence: 80%
“…5(b), are the key ingredient for entangling the systems. This highlights the significance of the two-qubit X-state environments (described by a state matrix in which only diagonal and antidiagonal entries are nonzero) [34,35]. Daǧ et al [23] encountered a similar result-they found that antidiagonal coherences in n = 3 qubit baths do not contribute to squeezing or displacement of a single cavity mode.…”
Section: General Case: Master Equations For N-qubit Environmentsmentioning
confidence: 80%
“…Those states arise naturally in quantum information theory in various aspects. See [1,26,29,30,31,32] for example. Notable examples include Greenberger-Horne-Zeilinger diagonal states, which are mixtures of GHZ states with noises.…”
Section: Introductionmentioning
confidence: 99%
“…Alluding to the pattern of nonzero matrix elements, states of this structure are known as X states (here, there are some additional zeros). X states have been widely studied [70][71][72][73][74][75][76] with respect to entanglement and other quantum properties, in particular a subset of these states, which is called GHZ-diagonal [77]. Despite their simple structure, states of this form yield a rich pattern in the map of entanglement classes as we will see in the following.…”
Section: Map Of Entanglement Classesmentioning
confidence: 99%